Effect of Welding Current and Electrode Movement on HAZ Width and Hardness of TIG Welded 304 Stainless Steel - Herdianto, Albertus Nova Tomy; Suheni, Suheni; Rosidah, Afira Ainur (Institut Teknologi Adhi Tama Surabaya, 2024)
Tungsten Inert Gas (TIG) welding is a welding technique using an electric arc between a non-consumable tungsten electrode and a shielding gas for the heat formation. This research aims to determine the comparison of the macro structure and hardness (Vickers) of 304 stainless steel in TIG welding with spiral, zig-zag and triangular electrode movements, as well as the welding current variatons of 60, 80, and 100 A. The results show that the welding current and movement affect the hardness and HAZ width of the welded 304 stainless steel using TIG welding process. The greater current leads to higher HAZ width and hardness. Furthermore, the spiral movement provides higher hardness due to its fast movement in welding which leads a faster cooling as well. The highest HAZ width reaches the value of 2.05 mm using the 100 A welding current and triangle movement. Meanwhile, the highest hardness is obtained in the value of 450.5 kgf/mm2 in the same current and movement.